Eur Oral Res 2021
DOI: 10.26650/eor.20210119
|View full text |Cite
|
Sign up to set email alerts
|

The antibacterial effects of vitamin D3 against mutans streptococci: an in vitro study

Abstract: Purpose This study aims to evaluate the antimicrobial effects of the cholecalciferol vitamin D 3 against Streptococcus sobrinus (Strep. sobrinus) and Streptococcus mutans (Strep. mutans) bacteria in vitro that is considered the main causative bacteria in dental caries development. Materials and Methods The antimicrobial effects of vitamin D3 were evaluated against Strep. sobrinus and Strep mutans using the agar disc diffusion method. The minimum inhibitory concentration (MIC) and minimum bactericidal concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 33 publications
0
9
1
Order By: Relevance
“…The MBC values obtained for both compounds in this study were 166 µg/ml and 83 µg/ml for Doxercalciferol and Cholecalciferol respectively. This contrasts with Almoudi et al [ 31 ], who reported the MBC for Cholecalciferol of 500 µg/ml. Several factors such as water solubility and polarity, which are influenced by preparation methods, may impact the Minimum Inhibitory Concentration (MIC) readings [ 35 , 36 ]).…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…The MBC values obtained for both compounds in this study were 166 µg/ml and 83 µg/ml for Doxercalciferol and Cholecalciferol respectively. This contrasts with Almoudi et al [ 31 ], who reported the MBC for Cholecalciferol of 500 µg/ml. Several factors such as water solubility and polarity, which are influenced by preparation methods, may impact the Minimum Inhibitory Concentration (MIC) readings [ 35 , 36 ]).…”
Section: Discussioncontrasting
confidence: 74%
“…Recently, Cholecalciferol (D3) was shown to be effective against S. mutans and Streptococcus sobrinus . Scanning Electron Microscope (SEM) analysis reported that both microorganisms presented morphological changes following the application of D3 [ 31 ]. Vitamin D compounds may be promising for the prevention of carious lesions.…”
Section: Introductionmentioning
confidence: 99%
“…230 An imbalance in vitamin D-mediated functions due to its relative deficiency could further put the body at an increased risk of infection. 232,233 Aggressive forms of periodontitis were found to be associated with high serum 25(OH)D3 levels and its binding protein.…”
Section: Expression Of Cap Cemp1 Bsp Ocnmentioning
confidence: 99%
“…Furthermore, triggering receptor expressed on myeloid cells‐1 (TREM‐1), a pivotal amplifier of the innate immune response in macrophages, was upregulated 16 folds, and the activation on the gingival epithelial cells increased their IL‐8 mRNA levels, with antimicrobial activity against A. actinomycetemcomitans 230 . An imbalance in vitamin D‐mediated functions due to its relative deficiency could further put the body at an increased risk of infection 232,233 . Aggressive forms of periodontitis were found to be associated with high serum 25(OH)D3 levels and its binding protein.…”
Section: Vitamins As Micronutrients In Periodontal Wound Healing/rege...mentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14][15][16] Qatari people, 18.75% of 5-12 years old American children, and 49.9% of 6-11 years old Canadian children suffered from vitamin D deficiency. This difference can be related to the difference in the age of samples, eating habits, oral health, and methods used for caries prevention(10)(11)(12).…”
mentioning
confidence: 99%